Ferraz de Vasconcelos - município da grande São Paulo: o desafio da descentralização das políticas públicas e o associativismo local - Carreira, Maria Olinda Costa Santos (2005)
This thesis is a case study of the city of Ferraz de Vasconcelos, one of the 39 cities of the Great São Paulo, ahead of the process of decentralization of the public politics and the democratization of the public space in local level. They had been taken as base authors who had studied these processes and its controversies in metropolis and the metropolisation of the poverty. The city of Ferraz de Vasconcelos was formed from a nucleus of people in the end of century XIX and beginning of century XX In the place, at the time of its formation, had been fixed immigrant of some nationalities, that had dedicated the plantation to it of fruits, had acclimatized per fifteen years dumb of the grape italy and had initiated its commercial plantation in 1942. From middle of years 50, a small cycle of industrialization, raised in the decade of 70, and stagnated in the city in the following decade. From years 70, the decline of the commercialization of the grape italy was initiated and, with the metropolisation of the poverty, the city passed to be looked by poured population groups, "expulses" of the city of São Paulo, in search of land divisions, regular or irregular and occupations. In years 90, in the place, joint habitationals of the CDHU had been constructed and the city was changed into bedroom town . With this new situation, it one ahead saw of great budgetary challenges and the process of decentralization of the public politics and had that to assume the role that was reserved to it in this process, although to present a level of sufficiently intense associativism. The local associativism had as characteristic important the religiosity and was influenced in years 80 and 90 for the Catholic Church, developing actions related to the CEBs and, more recently, for the Evangelicals Churches. The methodology of research used in this study was developed in three phases and appealed to some instruments: bibliographical research documentary and of statistical data, participant comment of meetings of some groups, advice of representation and events, interviews with old inhabitants, with militant, directors of entities and associations that participate of the social dynamics and the local politics. With the result of the analysis, it was possible to conclude that Ferraz de Vasconcelos, and probably other cities that have passed for similar trajectory, accumulated deficiencies that had been aggravated by the decentralization proposals. However, the city searches alternatives, the organized groups acts, but the results very are reduced of the point of view of the economic and social development